Pengaruh Konsentrasi Glukomanan (Amorphophallus Konjac) Terhadap Karakteristik Jelly Drink Wedang Jahe (Zingiber Officinale) - Karmila, Melly; Pratiwi, I Desak Putu Kartika; Widarta, I Wayan Rai (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 4 (2023): Jurnal ITEPA, 2023)
Ginger wedang was a traditional drink from Indonesia which can be further processed into jelly drink. Jelly drink are different from other types of gel products because jelly drink products are consumed by aspiration (flow) and immediately swallowed like a drink. Jelly drinks generally used carrageenan as a gelling agent but carrageenan has a weakness because has a high syneresis value, the addition of glucomannan can improve the gel properties that are formed into a strong and elastic gel and able to reduce gel syneresis. This research was conducted to determine the effect of adding glucomannan and to obtain the concentration of glucomannan which produces ginger wedang jelly drink with the best characteristics. The experimental design was a complete randomized design with one factor which are consisting 5 levels of glucomannan concentration, namely: 0.05%, 0.075%, 0.10%, 0.125%, 0.15% with three replications. The parameters tested are total soluble solids, syneresis, dietary fiber, and hedonic sensory test (taste, texture, easiness to swallowed, easiness consumed using straw, and overall acceptance). The data analyzed using Analysis of Variance (?=0.05) and continued by Duncan Multiple Range Test (?=0.05). The results showed that the concentration of glucomannan had a significant effect the total soluble solids, syneresis, dietary fiber, taste, texture, easiness to swallowed, easiness consumed using straw, and overall acceptance. The best characteristic of ginger wedang jelly drink was addition 0.1% glucomannan with the total soluble solids of 4.1%, syneresis of 3.91%, dietary fiber of 6.46%, and sensory acceptability are liked.